Evolution of Pediatric Home Mechanical Ventilation Program in Serbia—What Has Changed in the Last Decade - Basa, Mihail; Minic, Predrag; Rodic, Milan; Sovtic, Aleksandar (Frontiers in Pediatrics, 2020)
Home mechanical ventilation (HMV) is a method of treatment in children with sleep-disordered breathing (SDB) and alveolar hypoventilation regardless of primary disease. The goal of the study was to describe the changes in HMV program in Serbia during the last two decades. Cross-sectional retrospective study included data from national HMV database from 2001 until 2019. HMV was initiated in clinically stable patients after the failure to wean from mechanical ventilation succeeded acute respiratory deterioration, or electively after the confirmation of SDB and alveolar hypoventilation by sleep study or continuous transcutaneous capnometry and oximetry. The study included 105 patients (50 ventilated non-invasively, 55 ventilated invasively via tracheostomy). The median age at the time of HMV initiation was 6.2 years (range: 0.3–18 years). Invasive ventilation had been initiated significantly earlier than non-invasive ventilation (NIV) (p < 0.01), without difference in duration of ventilatory support (p = 0.95). Patients on NIV were significantly older (p < 0.01) than those ventilated invasively (13 and 1.5 years respectfully). Average waiting time on equipment had been shortened significantly – from 6.3 months until 2010 to 1 month at the end of the study (p < 0.01). Only 6.6% of patients had OSAS requiring HMV. During the study period 24% patients died, mostly due to uncontrolled infection or progression of underlying disease. Availability and shortened waiting time for the equipment accompanied by advanced overall health care led to substantial improvements in national HMV program. However, future improvements should be directed to systematic evaluation of SDB in patients with OSAS, early diagnosis of nocturnal hypoventilation, and subsequent timely initiation of chronic ventilation.